Characterisation of children and adolescents with acute lymphoblastic leukaemia who presented without peripheral blood blasts at diagnosis. (9th November 2022) - Mangum, David Spencer; Bishop, Johnathon D.; Zhou, Yinmei; Cheng, Cheng; Karol, Seth E.; Rubnitz, Jeffrey E.; Ribeiro, Raul C.; Yang, Jun J.; Mullighan, Charles G.; Jeha, Sima; Pui, Ching‐Hon; Inaba, Hiroto
Summary: Of 1003 children with acute lymphoblastic leukaemia (ALL), 147 (14.7%) presented without peripheral blood blasts (PBB). While absence of PBB was not independently associated with survival outcomes when compared to those with PBB, patients without PBB had distinct genetic and clinical characteristics. Notably, we identified a novel genotype–phenotype relationship, in that the patients without PBB had a significantly higher incidence of hyperdiploid B‐ALL, accounting for almost half of all patients without PBB (46.9% vs. 22.7%, p  < 0.001). Further, absence of PBB was associated with decreased rates of leukaemia involvement of the central nervous system ( p  < 0.001).